2003
DOI: 10.1086/376631
|View full text |Cite
|
Sign up to set email alerts
|

Listeriosis in Patients at a Comprehensive Cancer Center, 1955-1997

Abstract: Listeria monocytogenes infection occurred in 94 patients during 1955-1997 at Memorial Sloan-Kettering Cancer Center. The incidence was 0.5 (1955-1966), 0.96 (1970-1979), and 0.14 (1985-1997) cases per 1000 new admissions. Eighty-five patients (90%) were bacteremic, and 34 (36%) had evidence of intracranial infection. In 91 patients with cancer, 70 (77%) received chemotherapy for advanced or relapsed malignancy (n=51; 56%); 64 (68%) received corticosteroids. Breast cancer was the most common solid-organ cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 34 publications
3
20
0
3
Order By: Relevance
“…70,71,73 However, in vivo synergism has not been uniformly observed and retrospective clinical studies have not consistently shown better results for combined therapy of listeriosis than simple penicillin monotherapy. 3,4,70,74 In this review, 23 of 35 (65.7%) patients with listerial endocarditis treated with the combination of penicillin or ampicillin with aminoglycosides survived the infection in comparison with ten out of 14 (71.4%) treated with penicillin monotherapy. The combination of vancomicin with gentamicin was successfully used in four patients including one in the above case studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…70,71,73 However, in vivo synergism has not been uniformly observed and retrospective clinical studies have not consistently shown better results for combined therapy of listeriosis than simple penicillin monotherapy. 3,4,70,74 In this review, 23 of 35 (65.7%) patients with listerial endocarditis treated with the combination of penicillin or ampicillin with aminoglycosides survived the infection in comparison with ten out of 14 (71.4%) treated with penicillin monotherapy. The combination of vancomicin with gentamicin was successfully used in four patients including one in the above case studies.…”
Section: Discussionmentioning
confidence: 87%
“…2 Endocarditis is a rare complication of bacteremia due to Listeria and in the most recent series on listeriosis in adults, cases of endocarditis were not found. 3,4 However, infections occurring both on natural and prosthetic valves have been reported. 5,6 Due to the scarcity of these reports, the clinical manifestations, optimal treatment and outcome of listerial endocarditis have not been completely ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…The disease primarily affects the elderly, neonates, and immunocompromised individuals, which includes an increasing population of cancer and HIV-positive patients [1,5,6]. A positive outcome for listeriosis depends on the early administration of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, TMP-SMX is used in many transplant centers for varying durations (3 months to as long as a lifetime) primarily to prevent Pneumocystis pneumonia, and this combination is also effective against L. monocytogenes and T. gondii (Marty and Rubin, 2006;Fishman 2007;del Pozo, 2008;Muñ oz et al, 2010). The great majority of L. monocytogenes isolates from clinical and food sources were susceptible to TMP-SMX, but a very few isolates were resistant (Safdar and Armstrong, 2003;Conter et al, 2009;Morvan et al, 2010). Alternative prophylactic agents against Pneumocystis may have less activity against L. monocytogenes (Baden et al, 2001).…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%